2017
DOI: 10.5254/rct.82.83719
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Wax/Epdm Blends as Shape-Stabilized Phase Change Materials for Thermal Energy Storage

Abstract: Various amounts of a paraffinic wax were dispersed by melt mixing in an ethylene/propylene diene monomers (EPDM) rubber matrix. The resulting compounds were then vulcanized to obtain shape-stabilized rubbery phase change materials for thermal energy storage. The addition of the paraffinic wax induced a retardation in the vulcanization kinetics of the EPDM matrix. Calorimetric measurements evidenced how the homogenous distribution of the wax domains within the rubber, confirmed by electron microscopy observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Among organic PCMs, paraffin waxes are the most widely used in TES applications, especially because of their elevated energy density, narrow working temperature range, versatility, lightness, and cheapness . Thanks to these peculiar features, TES systems based on PCMs can be successfully applied in buildings, smart textiles, solar plants, hot/cold water storage, and the thermal regulation of electronic devices . The most serious drawbacks of organic PCMs are their intrinsic limited thermal conductivity and the need for confinement to avoid leakage when above their melting point .…”
Section: Introductionmentioning
confidence: 99%
“…Among organic PCMs, paraffin waxes are the most widely used in TES applications, especially because of their elevated energy density, narrow working temperature range, versatility, lightness, and cheapness . Thanks to these peculiar features, TES systems based on PCMs can be successfully applied in buildings, smart textiles, solar plants, hot/cold water storage, and the thermal regulation of electronic devices . The most serious drawbacks of organic PCMs are their intrinsic limited thermal conductivity and the need for confinement to avoid leakage when above their melting point .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such fields can be the automotive, aerospace, portable electronics and technical garments industries. However, even though there are many examples in the literature of encapsulated and shape stabilized PCMs embedded in a polymer matrix [5,12,17,29,[39][40][41][42], only few papers can be found that deal with the development of polymer composites merging structural and TES functions. Most of the examples of such composites regard sandwich structures that have functions of thermal management with [22] or without [43,44] the use of a PCM.…”
Section: Introductionmentioning
confidence: 99%
“…If the shape stabilization is performed with a metallic or a carbon based material, this also leads to an increase of the overall thermal conductivity [27,28]. TES systems based on PCMs find applications in buildings [29,30], hot/cold water storage [31], solar thermal power plants [32], smart thermoregulating textiles [25,33], and thermal management of electronic devices [22]. In most of these applications, the TES function is performed by a dedicated added module, containing PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…wide phase transition temperature range, lightness and limited costs [23,24], paraffinic waxes are the most widely investigated [21,[25][26][27]. However, their relatively low thermal conductivity and the possible leakage above the melting point limit their applications in several technologies [28].…”
mentioning
confidence: 99%
“…Encapsulation in more stable polymer matrices [27,29] can be a solution to avoid their flow at elevated temperature, thus forming a shape-stabilized phase change material (SSPCM) [30]. Several SSPCMs with various polymer matrices such as high-density polyethylene (HDPE) [31,32], polypropylene (PP), acrylic resins, epoxy resins [33][34][35], poly(methylmethacrylate) (PMMA), poly urethane [36] block copolymer, ethylene-propylene diene monomer rubber (EPDM) [27], styrene-butadiene-styrene (SBS) triblock copolymer [32,37], polyvinylchloride (PVC) [38] were considered. In many cases, also the PCM stabilization through the addition of inorganic nanofillers was considered [37,39].…”
mentioning
confidence: 99%